2019
DOI: 10.1126/sciadv.aau1200
|View full text |Cite
|
Sign up to set email alerts
|

A year in the life of a giant ground sloth during the Last Glacial Maximum in Belize

Abstract: Stable isotope analysis of the first fossilized Eremotherium laurillardi remains from Belize offers valuable insights into the conditions within which this individual lived and its ability to adapt to the increasing aridity of the Last Glacial Maximum (LGM). Cathodoluminescence (CL) microscopy was used to identify chemical alteration of the tooth during fossilization. Results demonstrate that the inner orthodentin resists diagenesis, yielding potentially unaltered values. Using an intensive “vacuum milling” te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
(89 reference statements)
2
14
0
Order By: Relevance
“…The teeth of xenarthrans are formed mostly of dentine, regarded as more prone to diagenetic modification compared to enamel because of its higher organic content, lower hardness, and smaller crystallites (MacFadden et al, 2010), thus making enamel the preferred material for isotope analysis. Nevertheless, isotopic studies on teeth of extinct sloths have been performed, showing that such analysis is feasible on dentin as well (Kohn et al, 2005;Ruez, 2005;Domingo et al, 2012;França et al, 2014;Silva, 2015;Dantas et al, 2017;Larmon et al, 2019;Pansani et al, 2019;Oliveira et al, 2020;Tomassini et al, 2020). The teeth of megatheriid sloths are prismatic, hypsodont, with subrectangular to subtriangular transverse outline and bilobate occlusal surfaces formed by transversal sharp crests separated by a deep valley (Owen, 1861;Spillmann, 1948;Sicher, 1953;Cartelle & De Iuliis, 1995;Vizcaíno, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The teeth of xenarthrans are formed mostly of dentine, regarded as more prone to diagenetic modification compared to enamel because of its higher organic content, lower hardness, and smaller crystallites (MacFadden et al, 2010), thus making enamel the preferred material for isotope analysis. Nevertheless, isotopic studies on teeth of extinct sloths have been performed, showing that such analysis is feasible on dentin as well (Kohn et al, 2005;Ruez, 2005;Domingo et al, 2012;França et al, 2014;Silva, 2015;Dantas et al, 2017;Larmon et al, 2019;Pansani et al, 2019;Oliveira et al, 2020;Tomassini et al, 2020). The teeth of megatheriid sloths are prismatic, hypsodont, with subrectangular to subtriangular transverse outline and bilobate occlusal surfaces formed by transversal sharp crests separated by a deep valley (Owen, 1861;Spillmann, 1948;Sicher, 1953;Cartelle & De Iuliis, 1995;Vizcaíno, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The wide variation in carbon isotope values (nearly 4‰) between dentine layers is interpreted to be diagenetic and the alteration appears to affect each dentine layer differentially, as observed in Eremotherium (Larmon et al, 2019). Diagenesis is of special concern for Xenarthrans because they lack enamel, the most favorable (and typically least altered) source for stable isotope analysis.…”
Section: Stable Isotopesmentioning
confidence: 99%
“…While most stable isotope studies of mammals utilize tooth enamel and sloth teeth lack enamel, the orthodentine of sloth teeth which has not been diagenetically altered can be sampled to provide stable isotope data (Larmon et al, 2019). One advantage of sloth teeth is that they are evergrowing (hypselodont) so sampling the entire length of the tooth permits a determination of changes in their diet as well as climate through different seasons.…”
Section: Stable Isotopesmentioning
confidence: 99%
“…The Eremotherium tooth from Belize is from the Last Glacial Maximum (LGM) (26,975 ± 120 calibrated years before present). Stable isotope analysis of the tooth for its entire length for stable carbon and oxygen isotope analysis showed that the tooth recorded two wet seasons separated by one longer dry season and that this sloth was able to adapt its diet to survive the marked seasonality of the LGM (Larmon et al, 2019) (Fig. 1).…”
Section: Eremotherium Laurillardimentioning
confidence: 99%